Waddling on the Dark Side: Ambient Light Affects Attendance Behavior of Little Penguins. (April 2016) - Rodríguez, Airam; Chiaradia, André; Wasiak, Paula; Renwick, Leanne; Dann, Peter
Visible light on Earth largely comes from the sun, including light reflected from the moon. Predation risk is strongly determined by light conditions, and some animals are nocturnal to reduce predation. Artificial lights and its consequent light pollution may disrupt this natural behavior. Here, we used 13 years of attendance data to study the effects of sun, moon, and artificial light on the attendance pattern of a nocturnal seabird, the little penguin Eudyptula minor at Phillip Island, Australia. The little penguin is the smallest and the only penguin species whose activity on land is strictly nocturnal. Automated monitoring systems recorded individually marked penguins every time they arrived (after sunset) at or departed (before sunrise) from 2 colonies under different lighting conditions: natural night skylight and artificial lights (around 3 lux) used to enhance penguin viewing for ecotourism around sunset. Sunlight had a strong effect on attendance as penguins arrived on average around 81 min after sunset and departed around 92 min before sunrise. The effect of moonlight was also strong, varying according to moon phase. Fewer penguins came ashore during full moon nights. Moon phase effect was stronger on departure than arrival times. Thus, during nights between full moon and last quarter, arrival times (after sunset) were delayed, even though moonlight levels were low, while departure times (before sunrise) were earlier, coinciding with high moonlight levels. Cyclic patterns of moon effect were slightly out of phase but significantly between 2 colonies, which could be due to site-specific differences or presence/absence of artificial lights. Moonlight could be overridden by artificial light at our artificially lit colony, but the similar amplitude of attendance patterns between colonies suggests that artificial light did not mask the moonlight effect. Further research is indeed necessary to understand how seabirds respond to the increasing artificial night light levels.